"Binary oppositions of space (closed, open / familiar, hostile / real and imaginary) in the novels (Jirmati, Al-Masalla) by Nabil Suleiman." - بليدي, رزان; يعقوب البيطار,; زكوان العبدو , (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The place has its importance in literary studies represented in multi-directional angles, which made Ghaleb Halasa say: "When a literary work lacks spatiality, it loses its specificity, and thus its authenticity." The place is considered one of the basic components of the novel, so in this research I tried to study the place in my novel "Al-Masla, Jarmati", and I presented the dualities of place, and I also pointed out the connotations of place, and I ended this research with a conclusion and a list of sources and references, and I summarized in the conclusion the conclusions included in the research.